1998
DOI: 10.1002/(sici)1096-8652(199807)58:3<183::aid-ajh4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 indirectly enhances proliferation of 5-FU-treated human hematopoietic peripheral blood CD34+ cells

Abstract: Interleukin-12 (IL-12) or natural killer cell stimulatory factor (NKSF), has multiple effects on T lymphocytes and natural killer cells. In this study, the effect of IL-12 on human hematopoiesis was studied by analyzing the growth of CD34+ peripheral blood stem cells (PBSC), in steady state. In the presence of Epo, IL-12 alone or in combination with IL-3 or SCF had no effect on the formation of colonies from CD34+ cells. In culture with Epo, G-CSF, and IL-3, the effect of Flt3-ligand (FL) on CD34+ PBSC was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Although IL‐12 was originally identified as an activator of natural killer cells and of T lymphocytes (Kobayashi et al , 1989; Wolf et al , 1991; Stern et al , 1990; Gubler et al , 1991), our previous results have clearly demonstrated that this cytokine has the capacity to stimulate proliferation of primitive progenitor cells, in the presence of accessory cells (Grafte et al , 1998). The haemopoietic effects of IL‐12 are generally observed only in combination with other factors (Fardoun‐Joalland et al , 1995).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although IL‐12 was originally identified as an activator of natural killer cells and of T lymphocytes (Kobayashi et al , 1989; Wolf et al , 1991; Stern et al , 1990; Gubler et al , 1991), our previous results have clearly demonstrated that this cytokine has the capacity to stimulate proliferation of primitive progenitor cells, in the presence of accessory cells (Grafte et al , 1998). The haemopoietic effects of IL‐12 are generally observed only in combination with other factors (Fardoun‐Joalland et al , 1995).…”
Section: Discussionmentioning
confidence: 77%
“…The IL‐12 effect on human haemopoiesis remains unclear. This report was aimed at explaining previous results which have shown an IL‐12 effect on immature peripheral blood stem cells (PBSCs), only in the presence of CD34‐negative cells (Grafte et al , 1998). The potential synergism between IL‐12 and others cytokines, especially in early human haemopoiesis, was of particular interest.…”
mentioning
confidence: 99%
“…Fardoun-Joalland et al [ 23 ] and Grafte et al [ 24 ] studied the in vitro efficacy of IL-12, using normal human peripheral blood and bone marrow mononuclear cells, respectively. They showed that in combination with rhIL-3, erythropoietin, or G-CSF, rhIL-12 could significantly enhance the formation of cell colonies.…”
Section: Progress In the Understanding Of The Role Of Il-12 In Hematomentioning
confidence: 99%
“…Accordingly, PBSCT may enhance engraftment by producing cytokines and accelerating hematopoietic reconstitution, and clinical attention has recently focused on the in vivo secretion of hematopoietic growth factors following high-dose chemotherapy and PBSCT. Furthermore, recent studies have suggested that IL-12 may be involved in dierentiation of early resting hematopoietic progenitor cells, and that IL-12, like other hematopoietic factors, may be an inducer of growth and dierentiation of immature progenitor cells (Jacobsen et al 1993;Ogawa 1993;Fardoun-Joalland et al 1995;Grafte et al 1998;Grafte et al 1999). …”
Section: Introductionmentioning
confidence: 99%